Predicting users' intention towards using library self-issue and return systems - Siti Nadhirah Mohmed Razip; Siti Fatnin Abdul Kadir; Siti Nur Aishah Saim; Farah Nadia Mohd Dolhan; Nurshamimi Jarmil; Nurul Hasanah Md Salleh; Grunsin Rajin (2016)
This study aims to examine users' acceptance of library self-issue and return system by integrating Theory of Planned Behaviour (TPB)/Technology Acceptance Model (TAM) as the guiding principle. The research used a multiple regression for data analysis across a sample of 238 students. Their participation was purely voluntary. Empirical analysis confirmed that student's intention to use the library self-service by behavioural intentions and perceived usefulness. However, the subjective norm was found to be not significantly related to library self-issues and return system. This empirical results may benefit to the students and the librarians involved in self-issue and return system in library. The librarian could avoid a long queue of students in the library. For the students, they will be able to save time on borrowing or retuning the materials. This research offers a new findings compare to the previous study, where this research focus on undergraduate students in Malaysia. Next, the proposed framework could be used as a foundation for future research investigating students who had not applied the library self-service respond.